Use of aspartate aminotransferase in diagnosing periodontal disease: a comparative study of clinical and microbiological parameters - Barbosa e Silva, Emílio; Salvador, Sérgio Luís S; Fogo, José Carlos; Marcantonio, Rosemary Adriana Chierici [UNESP] (Nihon University School of Dentistry, 2003)
The objective of this study was to assess the association between the levels of enzyme aspartate aminotransferase (AST) in gingival crevicular fluid (GCF) with the BANA hydrolysis microbiological test (Perioscan) and clinical periodontal diagnostic measurements, such as bleeding on probing, plaque index, gingival index, probing depth, and attachment level in patients with chronic periodontitis using an enzymatic test (PocketWatch). One hundred and forty-seven sites were evaluated in 22 patients with a probing depth of > or = 5 mm at selected sites. AST and BANA enzymatic tests were carried out, and clinical parameters recorded. Pearson's chi-square and Fisher's exact tests were used for statistical analysis. There was no statistical correlation between AST levels and any of the analyzed parameters. The lack of any association between the factors studied does not indicate, however, that the latter cannot be used in diagnosing the actual periodontal condition of patients and/or sites. However, more research should be carried out to evaluate the true relationship between AST and periodontal disease.
Keywords: aspartate aminotransferase; diagnostic agent; n benzoylarginine 2 naphthylamide; adult; chi square distribution; comparative study; enzyme assay; enzymology; female; gingivitis; human; male; metabolism; middle aged; periodontics; periodontitis; Adult; Aspartate Aminotransferases; Benzoylarginine-2-Naphthylamide; Chi-Square Distribution; Enzyme Tests; Female; Gingival Crevicular Fluid; Humans; Male; Middle Aged; Periodontal Index; Periodontitis